Implementasi Website Rahayu River Tubing sebagai Media Promosi dan Reservasi bagi Wisatawan - Faisal Dharma Adhinata Adhinata; Diovianto Putra Rakhmadani; Alon Jala Tirta Segara; Nur Ghaniaviyanto Ramadhan (Politeknik Negeri Cilacap, 2022)
Community service aims to implement website-based information technology as a media for promoting Rahayu River Tubing tourism and its reservation. The attractions offered are Tubing, Pangasinan Waterfall, Pengkol Hill, and Pedestal View. Before this website, promotions were only carried out on social media, and reservations were still manual by contacting the manager directly. This community service method is by identifying problems, developing the Rahayu River Tubing website at the address http://rahayurivertubing.com, and evaluating activities. This activity was attended by 15 participants from the manager and tour guide held at the Rahayu River Tubing basecamp. At the end of the activity, feedback is given to evaluate this community service activity. There are five statements on the questionnaire with an average result of 99%. These results indicate that community service partners are delighted with the socialization and training on the use of the Rahayu River Tubing tourism website.